2014
DOI: 10.1111/acer.12564
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Is Longitudinally Associated with Lower Urinary Tract Symptoms Partially Via High‐Density Lipoprotein

Abstract: We show strong evidence there is longitudinal association of alcohol consumption with LUTS. The protective effect of light-moderate alcohol consumption on LUTS is in part modulated by HDL as a confounder, similar to its effect on coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…However, a longitudinal study on the volume of alcohol consumption in this environment is necessary to corroborate this assertion. This is in line with Suh et al, Lu, and Mo that reported a similar protective effect of light-moderate alcohol consumption on IPSS [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, a longitudinal study on the volume of alcohol consumption in this environment is necessary to corroborate this assertion. This is in line with Suh et al, Lu, and Mo that reported a similar protective effect of light-moderate alcohol consumption on IPSS [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…24 Also, researchers recently noticed that light-moderate alcohol consumption was associated with decreased likelihood of moderate-severe LUTS, whereas heavy alcohol consumption was associated with increased risk for LUTS in a dose-dependent manner in Korean males. 25 The current results shared partial consistency (Table 4) with previous studies in which daily alcohol consumption presented as a positive trend with LUTS and its subtypes though the associations did not reach to significance, 11,23 and men with 1-2 times per week drinking were much less likely to have OBS symptoms of LUTS. 12,14 Additionally, we also evaluated the association between the drinking years and LUTS (Table 1) which often was ignored in others studies.…”
Section: Discussionsupporting
confidence: 88%
“…Alcohol consumption has been shown in many studies to be associated with LUTS; however, it is not well known how alcohol affects the bladder tissue per se. The epithelial lining of the urinary bladder (urothelium) is especially vulnerable as it is exposed to alcohol and its metabolites on both the serosal (interface with blood) and apical (interface with urine) aspect; in the latter case for long periods of time due to urine storage.…”
Section: Alcoholmentioning
confidence: 99%